Increased levels of bombesin-like peptides in the lower respiratory tract of asymptomatic cigarette smokers. - Aguayo, S M; Kane, M A; King, T E, Jr; Schwarz, M I; Grauer, L; Miller, Y E (The Journal of Clinical Investigation, 1989)
Bombesin-related peptides are growth factors for a variety of cells, including normal human bronchial epithelial cells. An ELISA for bombesin-like peptides (BLP) has been devised using the MAb BBC353, which is specific for the biologically active carboxy-terminal fragment shared by all known BLP. Using this ELISA, we measured bronchoalveolar lavage (BAL) fluid levels of BLP in normal cigarette smokers (n = 15) and normal nonsmokers (n = 18). Smokers' BAL fluid contained increased levels of BLP, whether expressed in terms of BAL fluid volume (P = 0.0001) or protein content (P less than 0.05). BLP levels did not correlate with any cellular constituent in the BAL fluid but immunostaining of lung tissue with BBC353 revealed an intense specific staining of neuroendocrine cells, implying these as a potential source. Two peaks of bombesin-like immunoreactivity were purified using sequential reverse phase and gel filtration HPLC. Both BLP have apparent molecular weights similar to gastrin-releasing peptide on gel filtration HPLC analysis. However, the amino acid composition of these BLP is different from that of gastrin-releasing peptide or neuromedin B, the only known mammalian forms of BLP, suggesting either incomplete purification or novel peptides. Sequence analysis could not be performed due to blocking groups at the amino terminus of these peptides. Our data demonstrate that cigarette smoking is associated with increased levels of pulmonary BLP and imply a potential role for these neuropeptides in the lung's response to tobacco smoke. Images